New business models: Beyond the shareholder approach - Alcaniz, Leire; Aguado, Ricardo; Retolaza, Jose Luis (Review of Business Management, 2020)
Purpose – The first objective of this paper is to explain and compare new business models that are currently being successfully applied worldwide. The second objective is to carry out an empirical analysis to observe the perception of experts regarding these models, the differences between them, and their orientation toward the traditional theory of the firm or the stakeholder approach in some of the characteristic elements of the organizational structure of the firm. Design/methodology/approach – In a first step we conduct a literature review that compares the dominant theory of the firm (neoclassical model) with the stakeholder theory. Secondly, we present six additional business models and compare them with both the neoclassical and stakeholder approaches. In a second part of the paper we use a fuzzy Delphi methodology in order to collect qualitative information from a group of experts about those six additional business models. Findings – The stakeholder approach is a valuable explanatory tool to address how firms can generate a broader positive impact at the social level. Identifying the stakeholders that interact within the firm allows the firm’s managers to take into account their specific needs, which are usually not limited to profit maximization. Originality/value – Emerging business models can benefit from the stakeholder approach to integrate those needs due to an organizational structure focused on stakeholders’ interests.